Antimicrobial bisabolane-type sesquiterpenoids from the deep-sea sediment-derived fungus Aspergillus versicolor SD-330. Issue 22 (18th November 2021) - Li, Xiao-Dong; Li, Xin; Li, Xiao-Ming; Yin, Xiu-Li; Wang, Bin-Gui
Abstract: One new aromatic bisabolene-type sesquiterpenoid (1 ), along with four known analogues (2–5 ) were isolated and identified from the deep-sea sediment-derived fungus Aspergillus versicolor SD-330. Their structures were elucidated by NMR, HRESIMS, X-ray crystallographic analysis, and quantum chemical ECD calculations as well as comparison of those data with literature data. Compounds 1–5 were evaluated for antimicrobial activities against human and aquatic pathogenic bacteria. Compounds 1, 2 and 5 exhibited selective inhibitory activities against zoonotic pathogenic bacteria such as Aeromonas hydrophilia, Escherichia coli, Edwardsiella tarda and Vibrio harveyi, with the MIC values ranging from 1.0 to 8.0 μg/mL. Graphical Abstract: